2007
DOI: 10.1002/jcu.20359
|View full text |Cite
|
Sign up to set email alerts
|

Bladder ultrasound in the evaluation of the efficacy of dextranomer/hyaluronic acid injection for treatment of vesicoureteral reflux

Abstract: The identification of the implant in the subureteral region by bladder sonography correlated with resolution of reflux in the early postinjection period. On the other hand, the majority of the implants disappeared on sonography in the long term despite correction of reflux. Therefore, we believe that the use of bladder sonography is not useful in the evaluation of patients in long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…The same authors also estimated a positive predictive value (PPV) of 89% for the presence of mound on ultrasound imaging and prediction of VUR resolution at VCUG. Similar results were obtained by Ozcan et al [10] who suggested a PPV of 86.3% based on 19 of 22 ureters with an identifiable mound that had no VUR on VCUG.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The same authors also estimated a positive predictive value (PPV) of 89% for the presence of mound on ultrasound imaging and prediction of VUR resolution at VCUG. Similar results were obtained by Ozcan et al [10] who suggested a PPV of 86.3% based on 19 of 22 ureters with an identifiable mound that had no VUR on VCUG.…”
Section: Discussionsupporting
confidence: 89%
“…Unfortunately, VCUG remains a distressing and uncomfortable investigation for children and their parents, graved by concern for radiation exposure, particularly in children who should undergo long term followup examinations. Recently some authors identified ultrasound mound appearance as a potential predictor of success of the procedure [8][9][10]. Moreover many technical variables could play a role in determining successful outcome, such as ureteral hydrodistention, bladder filling, and height of the obtained mound.…”
mentioning
confidence: 99%
“…3). The examination was performed as described in published study by Özcan et al [16] All descriptive data are shown as means and standard deviation (SD), median or numbers (%). Performance characteristics were calculated as follows: sensitivity = (true positive)/(true positive + false negative); speci city = (true negative)/(true negative + false positive); positive predictive value (PPV) = (true positive)/(true positive + false positive); negative predictive value (NPV) = (true negative)/(false negative + true negative); accuracy = (true positive + true negative)/(true positive + false negative + true negative + false positive).…”
Section: Methodsmentioning
confidence: 99%
“…They also noticed that the febrile UTI rate was significantly higher in children on surveillance (57%) than on prophylaxis (19%) and endoscopic therapy (23%). Ozcan et al [17] reported on a 2D bladder ultrasound in the evaluation of the efficacy of Dx/HA injection for VUR treatment. The success rate of endoscopic reflux correction in this series was 88%.…”
Section: Discussionmentioning
confidence: 99%
“…These digitalized images facilitate comparisons within the follow-up measurements. There are a couple of studies concerning ultrasound examination in the follow-up of endoscopic therapy [7][8][9][10][11][12][13][14][15][16][17] . Sonography is noninvasive, without radiation burden and significant data are even available in incompliant children.…”
Section: Discussionmentioning
confidence: 99%